The value of helping The Story of Harriet Tubman - Johnson, Ann Donegan (Value Communications La Jolla, California, 1979)
Describes the helpful work of Harriet Tubman in aiding slaves to flee the South, in assisting the Union army during the Civil War, and in establishing homes for the old and needy aftr the war.
8 - 10 years
Keywords: Tubman, Harriet Ross -- 1815?-1913; Underground railroad -- Slavery in the United States -- Fugitive slaves; Slaves -- United States; Afro-Americans; Altruism